2012
DOI: 10.1038/bjc.2012.357
|View full text |Cite
|
Sign up to set email alerts
|

Dose banding as an alternative to body surface area-based dosing of chemotherapeutic agents

Abstract: Background:Dose banding is a recently suggested dosing method that uses predefined ranges (bands) of body surface area (BSA) to calculate each patient's dose by using a single BSA-value per band. Thus, drugs with sufficient long-term stability can be prepared in advance. The main advantages of dose banding are to reduce patient waiting time and improve pharmacy capacity planning; additional benefits include reduced medication errors, reduced drug wastage, and prospective quality control. This study compares do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 14 publications
(23 reference statements)
1
80
0
2
Order By: Relevance
“…This ascertainment could undermine the acceptance of DB built on BSA dosing. Regardless of the fact that some authors have shown no significant difference in precision (AUC versus target AUC in pharmacokinetic models) between using DB ranges and classic BSA dosing, the inaccuracy of BSA remains an important concern 15. This cannot be solved with DB.…”
Section: Discussionmentioning
confidence: 99%
“…This ascertainment could undermine the acceptance of DB built on BSA dosing. Regardless of the fact that some authors have shown no significant difference in precision (AUC versus target AUC in pharmacokinetic models) between using DB ranges and classic BSA dosing, the inaccuracy of BSA remains an important concern 15. This cannot be solved with DB.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy was feasible, since the difference in the calculated docetaxel dosage was marginal compared to regular BSA dosing. This strategy has the potential to simplify pharmacy processes and to improve patient safety [90].…”
Section: Bsa Dose Bandingmentioning
confidence: 99%
“…To improve the current BSA strategy, it was recently suggested that dose-banding could be an alternative [90]. A limited amount of predefined BSA ranges was used to determine an initial docetaxel dose and for adaptation of the dose in patients with extreme BSA values.…”
Section: Bsa Dose Bandingmentioning
confidence: 99%
“…Une modification plus profonde des pratiques peut aussi être envisagée en abandonnant la préparation magistrale au profit d'une approche plus industrialisée (dose-banding) [24,25] où le contrôle final peut être supprimé au profit des Process Analytical Technology (PAT) [26]. Une réorganisation géogra-phique sous forme de plates-formes régionales peut aussi être une solution intéressante.…”
Section: Retrait De Lotunclassified